2006
DOI: 10.2337/db05-1183
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Muscle Strength and Quality in Older Adults With Type 2 Diabetes

Abstract: Adequate skeletal muscle strength is essential for physical functioning and low muscle strength is a predictor of physical limitations. Older adults with diabetes have a twoto threefold increased risk of physical disability. However, muscle strength has never been investigated with regard to diabetes in a population-based study. We evaluated grip and knee extensor strength and muscle mass in 485 older adults with diabetes and 2,133 without diabetes in the Health, Aging, and Body Composition study. Older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
515
8
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 637 publications
(594 citation statements)
references
References 40 publications
36
515
8
15
Order By: Relevance
“…The Health, Aging, and Body Composition Study (Health ABC) was designed to investigate the impact of changes in body composition and health conditions on age-related physiological and functional status among adults from 70 to 79 years of age. In this cohort, we have reported that older adults with type 2 diabetes had lower skeletal muscle strength and quality (12). However, it is still unclear whether lower muscle strength in diabetes is a consequence of diabetes or just a coincidence because previous studies were cross-sectional observations.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The Health, Aging, and Body Composition Study (Health ABC) was designed to investigate the impact of changes in body composition and health conditions on age-related physiological and functional status among adults from 70 to 79 years of age. In this cohort, we have reported that older adults with type 2 diabetes had lower skeletal muscle strength and quality (12). However, it is still unclear whether lower muscle strength in diabetes is a consequence of diabetes or just a coincidence because previous studies were cross-sectional observations.…”
mentioning
confidence: 75%
“…The Health ABC Study was described in detail elsewhere (12). Among 2,618 participants who had completed baseline assessments for skeletal muscle mass and strength, 1,840 (70.3%) were reexamined 3 years later.…”
mentioning
confidence: 99%
“…Some studies have also shown that older diabetic individuals have an accelerated loss of skeletal muscle strength (23,24), which is more pronounced among those with poor glycemic control (HbA1c>8%) (25). Still, to our knowledge only one previous study has evaluated the role of hyperglycemia in frailty development.…”
Section: Discussionmentioning
confidence: 99%
“…First, neuromuscular function assessment was focused exclusively on respiratory muscles, thus leaving potential peripheral muscle impairment unexplored. Nonetheless, numerous studies have demonstrated that peripheral muscle impairment occurs in diabetic patients and is related to the severity of diabetic polyneuropathy [1][2][3][4]. Furthermore, it remains uncertain whether nerve disorder as such, neuromuscular cross-link disorders, downstream muscle dysfunction or a combination of different pathologies are responsible for impaired muscle force generation.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle weakness is well-recognised as an important clinical manifestation of diabetic polyneuropathy [1] and is related to the severity of this condition [1][2][3][4]. In addition, diabetes has a major negative impact on intensive care unit outcome [5,6], including prolonged weaning from mechanical ventilation [7].…”
Section: Introductionmentioning
confidence: 99%